The Role of Technopreneurship Education in Increasing Student Entrepreneurial Interest and Competence - Sutrisno Sutrisno (Politeknik Ganesha Medan, 2023)
In the era of globalisation and advances in information technology, entrepreneurship has become one of the key factors in driving a country's economy. Technological developments have also opened up new opportunities for individuals to create technology-based innovations, known as technopreneurship. The purpose of this study is to analyse the role of technopreneurship education in increasing students' entrepreneurial interest and competence. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The results show that the role of technopreneurship education in increasing students' entrepreneurial interest and competence is very important and has a wide impact. Technopreneurship education brings positive impacts not only on individual students, but also on society and the economy as a whole. By combining technology and entrepreneurship, it equips students with the necessary knowledge, skills and mentality to become successful entrepreneurs in the digital and innovation era.